Advances in Cardiotoxicity Induced by Altered Mitochondrial Dynamics and Mitophagy - Yin, Yiyuan; Shen, Haitao (Frontiers in Cardiovascular Medicine, 2021)
Mitochondria are the most abundant organelles in cardiac cells, and are essential to maintain the normal cardiac function, which requires mitochondrial dynamics and mitophagy to ensure the stability of mitochondrial quantity and quality. When mitochondria are affected by continuous injury factors, the balance between mitochondrial dynamics and mitophagy is broken. Aging and damaged mitochondria cannot be completely removed in cardiac cells, resulting in energy supply disorder and accumulation of toxic substances in cardiac cells, resulting in cardiac damage and cardiotoxicity. This paper summarizes the specific underlying mechanisms by which various adverse factors interfere with mitochondrial dynamics and mitophagy to produce cardiotoxicity and emphasizes the crucial role of oxidative stress in mitophagy. This review aims to provide fresh ideas for the prevention and treatment of cardiotoxicity induced by altered mitochondrial dynamics and mitophagy.